PENENTUAN NILAI RUJUKAN LAJU ENDAP DARAH PADA WANITA USIA 20-50 TAHUN - Nuraeni, Hanny Siti; Astriani, Ranti Dwi; Shufiyani, Shufiyani; Destriana, Destriana (jitek, 2023)
ESR (Erythrocyte Sedimentation Rate) is one of the parameters used for health checks. The ESR value is used to determine the presence of inflammation and infection and monitor disease. The reference value is an examination used to see a normal rather than a laboratory examination of a patient. The problem is that the current ESR reference values ​​refer to lab parameter insert kits and WHO, where reference values ​​may vary between geographic regions, age groups, gender and race. Based on the International Council for Standardization in Hematology (ICSH) and ISO 15189 Clause 5.2.2, the range of reference values ​​must be stated based on the local area minimum of 120 samples. The population used in this research was Periuk sub-district, Tangerang City, is 191 and the sample was 126 people with a random sample. Determining the reference value range in this study used primary data using statistical calculations based on CLSI EP28-A3C guidelines, namely the 2.5 and 97.5 percentiles. The research results obtained a degree of ESR reference values ​​of 0-39 mm/hour. Suggestions for further research are to determine reference values ​​based on gender and racial distance.